Kepemimpinan dan Budaya Organisasi terhadap Kinerja Pengajar - Rahmat Santoso; Alvian Demaz Peramutya; Anicitus Agung Nugroho; Imam Safi’i (IPM2KPE, 2022)
This study aims to determine the relationship between leadership and organizational culture on the performance of the Banten Shipping Polytechnic instructor. The method used is descriptive quantitative with a sample of 40 teachers at Poltekpel Banten. Data was collected through questionnaires distributed via google form. The results showed that there was a positive influence between leadership and teacher performance, between organizational culture and teacher performance, and between leadership and organizational culture. Good leadership will affect organizational culture and teacher performance will be good too. Just as a good organizational culture will also have a good effect on teacher performance. That way, teachers are motivated and become loyal to the organization. In conclusion, leadership, organizational culture, and teacher performance influence each other. Keywords: Organizational Culture, Work Leadership, Teacher Performance